2017
DOI: 10.1515/reveh-2016-0059
|View full text |Cite
|
Sign up to set email alerts
|

Electronic cigarettes and indoor air quality: a review of studies using human volunteers

Abstract: AbstractObjective:This paper is primarily aimed to review articles on electronic cigarettes (e-cigarettes) focusing on indoor air quality (IAQ) assessment that were conducted using human volunteers under natural settings that mimic actual vaping scenarios. Such studies may give a better representation of the actual potential exposure towards e-cigarettes emissions in indoor settings.Methods: Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 68 publications
0
13
0
1
Order By: Relevance
“…Reviews on e-cigarettes have summarized e-cigarette development (Cooke et al 2015;Glasser et al 2017), their impact on decreasing smoking use (Kalkhoran and Glantz 2016;Rahman et al 2015), health and physiological effects Pisinger and Døssing 2014;Zucchet et al 2017), and effects of vaping on indoor air quality (Fernández et al 2015;Zainol Abidin et al 2017). Some of these reviews reported on metal levels; in addition, two systematic reviews have specifically evaluated metals/metalloids in cig-a-like cartomizers (Mishra et al 2017) and in e-cigarette aerosols (Gaur and Agnihotri 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Reviews on e-cigarettes have summarized e-cigarette development (Cooke et al 2015;Glasser et al 2017), their impact on decreasing smoking use (Kalkhoran and Glantz 2016;Rahman et al 2015), health and physiological effects Pisinger and Døssing 2014;Zucchet et al 2017), and effects of vaping on indoor air quality (Fernández et al 2015;Zainol Abidin et al 2017). Some of these reviews reported on metal levels; in addition, two systematic reviews have specifically evaluated metals/metalloids in cig-a-like cartomizers (Mishra et al 2017) and in e-cigarette aerosols (Gaur and Agnihotri 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Comparatively little is still known regarding the risks of exposure to second-hand e-cigarette emissions, to bystanders. Different approaches have been described to estimate the exposure of bystanders, reviewed by Fernandez et al [2] and Abidin et al [3]. Some estimates have been based on a chemical analysis of machine-generated e-cigarette vapor.…”
Section: Introductionmentioning
confidence: 99%
“…At the time of the study, there were no e-cig data available on CRST nor among AI/ANs nationwide 41. e-Cig and tobacco cigarette consumption had a similar effect on cotinine concentrations in both active smokers and non-smokers with SHS 42–44. Recent data among AI/AN smokers confirmed that active tobacco cigarette smoking and e-cig use both generated comparable salivary cotinine levels 45…”
Section: Discussionmentioning
confidence: 98%